State and Islamic Holidays in Kabardino-Balkaria: Past and Present - A. A. Tatarov (Научный диалог)
This article presents a historical analysis of the Russian government’s policies regarding Islamic holidays over the past century, focusing on the case of Kabardino-Balkaria. Drawing on archival and published data, the author highlights the influence of historical legacies established during the Soviet era. It is noted that in the 1920s, Islamic holidays in Kabardino-Balkaria were officially recognized as non-working days for the first time. The study pays particular attention to the activities of the Council for Religious Affairs and the Council for Religious Cults during the 1940s to 1980s. Utilizing reporting documents, it introduces data on governmental tactics, as well as information regarding the number of participants, venues, and the gender composition of Muslims who observed fasting and engaged in communal celebrations. The article argues that for Muslims in Soviet Kabardino-Balkaria, the holidays of Uraza-Bayram and Kurban-Bayram became institutions for preserving religious practices amidst stringent secularism. Additionally, it examines the period of Islamic revival in the post-Soviet era, during which these holidays regained their status as regional non-working days. The findings demonstrate that government authorities and local self-governance bodies, along with political actors, actively participate in organizing these celebrations within the framework of identity politics and the regulation of public events.